THE IMPACT OF FOOD COMMODITY PRICES ON INFLATION IN BEKASI - Rohimuddin; Jihad Lukis Panjawa (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This research aims to examine the influence of price fluctuations on volatile food commodities such as rice, chilies, and meat in Bekasi. This research is quantitative study with the use of secondary data taken from Strategic Food Price Information Center in Bekasi in the form of commodity food prices from all markets. The data taken are meat, chilies, and rice price data in all markets in Bekasi City in the 2018-2022 period. The data analysis method used in this study is Vector Autoregression (VAR) analysis. Based on the results obtained that in the short term there are several variables that affect inflation in Bekasi City inflation two months earlier, inflation five months earlier, inflation eight months earlier, rice prices one month earlier, rice prices three months earlier, rice prices four months earlier, rice prices seven months earlier, cayenne pepper prices 2 months earlier, cayenne pepper prices 5 months earlier,  the price of cayenne pepper 8 months in advance, the price of beef 1 month in advance, the price of beef 3 months in advance, the price of beef 4 months in advance and the price of beef 6 months in advance. Meanwhile, long-term price inflation is also influenced by the price of rice, meat, and chilies.